Establishment of age-stratified serum vitamin B6 pyridoxal and pyridoxic acid reference intervals among children aged 1–16 years in Henan, china - Luan, Yusheng; Chen, Nan; Wang, Xucheng; Li, Xiaojuan; Yang, Junmei; Li, Tiewei (Frontiers in Nutrition, 2025)
Background/ObjectiveThe development of population-specific reference intervals (RIs) for serum vitamin B6 (B6) in Chinese pediatric populations has not been established. Current clinical practice relies on international thresholds, but diagnostic sensitivity with domestic biochemical profiles remains suboptimal. This study aims to establish age-stratified reference intervals for serum vitamin B6 pyridoxal (B6-PL) and pyridoxic acid (B6-PA) in Henan children aged 1–16 years.MethodsThis retrospective study analyzed 1,458 healthy children undergoing routine physical examinations at Henan Children’s Hospital from December 2021 to June 2024. Serum B6-PL and B6-PA were quantified using the Xevo TQ-S Micro liquid chromatography-tandem mass spectrometry system (Waters Corporation). Non-normally distributed data are expressed as median interquartile range (IQR) [M (P25, P75)]. Age- and sex-related differences were assessed using Mann-Whitney U or Kruskal-Wallis tests.ResultsAnalysis revealed that age significantly influences serum levels of B6-PL and B6-PA in children, while gender showed no significant effect. The pediatric cohort demonstrated a male predominance (58.98%, 860/1458) with a notable prepubertal skew (93.28%, 1360/1458 aged < 12 years). Further analysis facilitated the establishment of RIs for B6-PL and B6-PA across different age groups. The RIs for B6-PL were 1.62–17.70 ng/mL for children aged 1–5 years, 1.39–15.15 ng/mL for children aged 6–11 years, and 1.06–14.30 ng/mL for children aged 12–16 years. The RIs for B6-PA were 1.20–5.46 ng/mL for children aged 1–5 years, 1.10–4.41 ng/mL for children aged 6–11 years, and 0.95–4.99 ng/mL for children aged 12–16 years.ConclusionThis study establishes the first age-stratified RIs for serum vitamin B6 metabolites (B6-PL and B6-PA) among children aged 1–16 years in Henan, China.